2016
DOI: 10.7763/ijcea.2016.v7.561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ZnO and NiO Modified HZSM-5 Catalyst for Ethanol Conversion to Hydrocarbons

Abstract: Abstract-A series of NiO/ZnO/HZSM-5 catalysts were prepared by impregnation method with varying ZnO loading ranging from 0-2 wt% and keeping 4 wt% NiO loading constant. It was found that the ZnO/NiO modified HZSM-5 catalyst was highly active and selective towards ethanol conversion to hydrocarbons at 410 °C, WHSV = 3.5 hr -1 and pressure = 1 atm. A comparison has been done to study conversion and yield of different wt% of ZnO/NiO over HZSM-5 catalyst. The performance of catalysts was evaluated by conducting ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 32 publications
(28 reference statements)
2
7
0
Order By: Relevance
“…This is like the XRD pattern reported by Zhao for the peak of Zn/ZSM-5 catalysts [11]. The other studies also showed a peak at 2θ=23° for the peak of ZnO/ZSM-5 catalysts [6,23,24]. The main peak of each catalyst is ZZ (I) was obtained at 2θ=23.04°, 2θ=23.27° and 2θ=23.9°, then the ZZ (II) catalyst was obtained at 2θ=23.07°, 2θ=23.29°, and 2θ=23.93°.…”
Section: Xrd Analysissupporting
confidence: 86%
See 4 more Smart Citations
“…This is like the XRD pattern reported by Zhao for the peak of Zn/ZSM-5 catalysts [11]. The other studies also showed a peak at 2θ=23° for the peak of ZnO/ZSM-5 catalysts [6,23,24]. The main peak of each catalyst is ZZ (I) was obtained at 2θ=23.04°, 2θ=23.27° and 2θ=23.9°, then the ZZ (II) catalyst was obtained at 2θ=23.07°, 2θ=23.29°, and 2θ=23.93°.…”
Section: Xrd Analysissupporting
confidence: 86%
“…The catalyst surface area decreases as the amount of ZnO in catalyst increases. This may be due to metal oxide particles (ZnO) covering part of the surface of the catalyst so that the results of calculations by the tool show that the surface area of the catalyst is getting smaller [23,24]. This can be seen in the ZZ (III) catalyst which contains the most ZnO than other catalyst but has the smallest area (SBET = 188.490 m2/g).…”
Section: N 2 Adsorption -Desorption With Bet -Bjh Methodsmentioning
confidence: 99%
See 3 more Smart Citations